2004
DOI: 10.1111/j.1439-0329.2004.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Armillaria ostoyae to forest soil microfungi

Abstract: Fungi isolated from the oak (Quercus robur) rhizosphere were tested for their effects on rhizomorph formation and growth of 16 isolates of Armillaria ostoyae sampled in three localities in western Poland. The number of rhizomorphs, number of rhizomorph apices, and rhizomorph length and weight increased most in the presence of Penicillium lanosum, Penicillium notatum, Cylindrocarpon destructans, Penicillium spinulosum and Mycelium radicis atrovirens a and, to a lesser extent, in the presence of Nectria grammico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…This suggests the possibility of variation in (i) biochemical properties of saprotrophic microfungi or (ii) differences in sensitivity of Armillaria to microbial stimuli depending on its origin. Variation in the sensitivity of A. ostoyae isolates to forest soil fungi relating to the physical and chemical conditions of its former habitat was reported previously (Kwaśna et al., ).…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…This suggests the possibility of variation in (i) biochemical properties of saprotrophic microfungi or (ii) differences in sensitivity of Armillaria to microbial stimuli depending on its origin. Variation in the sensitivity of A. ostoyae isolates to forest soil fungi relating to the physical and chemical conditions of its former habitat was reported previously (Kwaśna et al., ).…”
Section: Discussionsupporting
confidence: 55%
“…Kwaśna (2001, 2002, 2003a,b) and Kwaśna et al. (, ) showed that microfungi from roots and rhizosphere of oak stumps can stimulate the formation and growth of Armillaria rhizomorphs in vitro, in a substrate of natural forest soil. Aspergillus kanagawaensis Nehira, Cylindrocarpon didymum (Harting) Wollenw., Hormiactis candida Höhn, M. macrocystis , Mycelium radicis atrovirens Melin, Ilyonectria radicicola , P. adametzii , P. daleae , P. janczewskii , Penicillium lanosum Westling , Penicillium notatum Westling, P. spinulosum , Sporothrix schenckii var.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations